Plant-Mediated Green Route to Copper Oxide Nanoparticle Synthesis with Calotropis gigantea - Dayana, K. Sofiya; Jeyaseeli, P.; Mani, R. Jothi (Current Research Progress in Physical Science Vol. 9, 2025)
A facile, innovative and affordable green route has been demonstrated for the formation of Copper oxide nanoparticles by a biogenic method using aqueous leaf extract of calotropis gigantea which acts as a reducing and stabilizing agent. Copper nanoparticles received much attention owing to their high electrical conductivity, high liquefaction point, low electrochemical migration behavior, and low cost. The property of copper nanoparticles mainly depends on the synthesis route and their process parameters. The prepared Copper oxide nanoparticles were characterized by a host of different techniques such as X-ray diffraction (XRD), Diffuse reflectance spectroscopy (DRS), Zeta potential and Fourier transform infrared spectroscopy (FT-IR). The XRD pattern confesses that Copper oxide nanoparticles are associated with orthorhombic structure. The DRS absorption spectrum shows band gap energy corresponds to a wide band gap semiconductor The FT-IR spectra indicate the presence of chemicals which are responsible for the biochemical reaction. The Zeta Potential value revealed the stability of Copper oxide nanoparticles. Thermo-Gravimetric Analysis (TG) and Differential Thermal Analysis (DTA) are used as thermoanalytical techniques to study the synthesized NPS.